Liver X receptor inhibition potentiates mitotane-induced adrenotoxicity in ACC. Issue 6 (June 2020) - Warde, Kate M; Schoenmakers, Erik; Ribes Martinez, Eduardo; Lim, Yi Jan; Leonard, Maeve; Lawless, Sarah J; O'Shea, Paula; Chatterjee, Krishna V; Gurnell, Mark; Hantel, Constanze; Dennedy, Michael Conall
Abstract : Adrenocortical carcinoma (ACC) is a rare aggressive malignancy with a poor outcome largely due to limited treatment options. Here, we propose a novel therapeutic approach through modulating intracellular free cholesterol via the liver X receptor alpha (LXRα) in combination with current first-line pharmacotherapy, mitotane. H295R and MUC-1 ACC cell lines were pretreated with LXRα inhibitors in combination with mitotane. In H295R, mitotane (20, 40 and 50 µM) induced dose-dependent cell death; however, in MUC-1, this only occurred at a supratherapeutic concentration (200 µM). LXRα inhibition potentiated mitotane-induced cytotoxicity in both cell lines. This was confirmed through use of the CompuSyn model which showed moderate pharmacological synergism and was indicative of apoptotic cell death via an increase in annexinV and cleaved-caspase 3 expression. Inhibition of LXRα was confirmed through downregulation of cholesterol efflux pumps ABCA1 and ABCG1 ; however, combination treatment with mitotane attenuated this effect. Intracellular free-cholesterol levels were associated with increased cytotoxicity in H295R ( r 2 = 0.5210) and MUC-1 ( r 2 = 0.9299) cells. While both cell lines exhibited similar levels of free cholesterol at baseline, H295R were cholesterol ester rich, whereas MUC-1 were cholesterol ester poor. We highlight the importance of LXRα mediated cholesterol metabolism in the management of ACC, drawing attention to its role in the therapeutics of mitotane sensitive tumours. We also demonstrate significant differences in cholesterol storage between mitotane sensitive and resistant disease.